Criticism of Taklik Talak as an Effort to Protect Women in Marriage Law in Indonesia - Harry Yuniardi; Laras Shesa; Hamza Abed Alkarim Hammad (Madania: Jurnal Kajian Keislaman, 2024)
This study aims to analyze and critique the taklik talak statement, which is considered an effort to protect women's rights within positive law in Indonesia. The central question of this critique is whether a reform of Islamic family law is necessary as an effort to unify marriage law, elevate the status of women in marital relations, and respond to the consequences of societal developments. This research is descriptive in nature, as the data collected consists of texts, words, or descriptions derived from literature and library studies. It analyzes legal regulations related to the empowerment and protection of women's rights. The findings of the study suggest that if taklik talak is to be maintained as a manifestation of protection for women, its wording should be revised to more clearly reflect its support for women. The wife, as the victim, should not only be able to free herself from the bond of her husband, who has violated the taklik talak, but should also be entitled to compensation. Legal reform related to taklik talak in Indonesia is urgently needed. A commitment from various stakeholders, including the government, non-governmental organizations, and the general public, is required to address existing challenges. It is hoped that this will lead to the creation of a more just legal system that protects women's rights. Penelitian ini bertujuan untuk menganalisa dan mengkritisi kalimat taklik talak yang dinilai sebagai upaya perlindungan perempuan dalam hukum positif di Indonesia. Pertanyaan yang menjadi bahasan utama dari kritis tersebut adalah apakah diperlukan pembaruan hukum keluarga Islam sebagai upaya untuk melakukan unifikasi hukum perkawinan, meningkatkan status perempuan dalam relasi rumah tangga, bahkan sebagai respon terhadap ekses dari perkembangan zaman. Penelitian ini bersifat deskriptif karena data yang di himpun berbentuk teks, kata atau penggambaran yang berasal dari kajian kepustakaan dan literature. Dengan menganalisis regulasi perundang-undangan, yang terkait dengan hak pemberdayaan dan perlindungan perempuan. Hasil penelitian mengemukakan bahwa, jika memang taklik talak akan dipertahankan sebagai pengejwantahan perlindungan terhadap perempuan, maka redaksi taklik talak sudah seharusnya direvisi agar benar-benar nampak keberpihakannya kepada perempuan. Isteri sebagai korban, selain bisa lepas dari ikatan suaminya sebagai pelaku pelanggaran taklik talak, seharusnya juga harus mendapatkan kompensasi. Reformasi hukum terkait taklik talak di Indonesia sangat diperlukan. Dibutuhkan komitmen dari berbagai pihak, baik pemerintah, lembaga swadaya masyarakat, maupun masyarakat luas, untuk mengatasi berbagai kendala yang ada. Dengan demikian, diharapkan dapat tercipta sistem hukum yang lebih adil dan melindungi hak-hak perempuan.